From Sustainability-Oriented Innovation to Circular Outcomes: Evidence from SMEs - Doli Muhammad Ja’far Dalimunthe; Arif Qaedi Hutagalung; Dany Perdana Sitompul; Muhammad Dharma Tuah Putra Nasution (Yayasan Sinergi Kawula Muda, 2026)
Sustainability transitions in small and medium-sized enterprises (SMEs) depend on more than innovation intent — they require business models capable of translating that intent into product-level outcomes. This study tests an integrated model linking sustainability-oriented innovation (SOI), sustainable business model innovation (SBMI), barriers to the circular economy (B-CE), and sustainable product innovation performance (SPIP), with market performance (MP) as the downstream outcome. B-CE is positioned as both a suppressor of business model renewal and a moderator of the link between renewal and product-level output. Survey data from 280 Indonesian SMEs across sectors were analyzed using PLS-SEM. All eight hypotheses were supported (p < 0.001), with large effect sizes across the endogenous constructs (R² = 0.646–0.719). The study's principal contribution lies in empirically specifying SBMI as a necessary mediator between innovation orientation and product outcomes — a relationship prior literature had proposed conceptually but never tested within an integrated, SME-level model. B-CE operates in a dual capacity: as a direct suppressor of SBMI (β = −0.519) and as a moderator weakening the SBMI–SPIP relationship (β = −0.288), with the conditional slope falling from 0.717 under low-barrier conditions to 0.141 under high-barrier conditions. Structural relationships remained broadly consistent across sectors — manufacturing, service, and trading — and firm size, with only two of eighteen multigroup comparisons reaching significance. For managers and policymakers, cultivating sustainability orientation without reconfiguring value architecture is unlikely to yield measurable gains, and reducing circular economy barriers matters as much as direct innovation investment.